Sustainable and Energy-Efficient Building Design for Soldiers’ Accommodation in Pakistan - Ullah, Aman; Butt, Anosh Nadeem; Shah, Mir Wali; Quddusi, Syeda Arfa; Eryildiz, Demet Irkli (Departement of Architecture, Universitas Islam Indonesia, 2025)
In hot, arid regions like Jacobabad, Pakistan, military barracks must be sustainable and energy-efficient. This study investigates architectural techniques to improve energy efficiency while maintaining the comfort of military soldiers. The research is guided by a systematic process that includes experimental design, climate assessment, case study analysis, and energy performance modelling. Case studies and climate analyses are crucial elements in detecting environmental issues like excessive heat and sun radiation. The Hourly Analysis Program (HAP) and Building Information Modeling (BIM) are used in energy performance modelling to assess the effects of ventilation, shading, insulation, and orientation. Materials, window locations, and shading strategies are evaluated using a design of experiments (DOE) framework. The integration of renewable energy sources, especially solar photovoltaic panels, and passive cooling techniques are given top priority in this study. Practicality is ensured by validation and optimization, which results in a framework for military accommodations that use less energy and are more sustainable in harsh environments.